2020
DOI: 10.3168/jds.2019-17631
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of methicillin-resistant (mecA gene) and heat-resistant Staphylococcus aureus strains in pasteurized camel milk

Abstract: Staphylococcus aureus is a significant opportunistic pathogen in humans, dairy cattle, and camels. The presence of antibiotic-resistant and heat-resistant bacteria in camel milk has become a potential public health issue. The phenotypic and molecular characterization of methicillin-resistant staphylococcal strains recovered from pasteurized camel milk distributed in retail markets of Saudi Arabia was assessed. A total of 100 samples were collected between March and May 2017. Out of the 20 S. aureus isolates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 81 publications
0
14
0
Order By: Relevance
“…The majority of published reviews and studies conclude that there is no evidence to suggest that AMR bacteria are more heat tolerant than non-AMR bacteria, with the exception of three studies [ 51 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of published reviews and studies conclude that there is no evidence to suggest that AMR bacteria are more heat tolerant than non-AMR bacteria, with the exception of three studies [ 51 , 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the Salmonella strains used, an AMR strain of S. Typhimurium 2470 on beef and lamb, and AMR strains of S. Heidelberg (329 and 2581) on lamb were more heat resistant than other strains. A study of heat resistant MRSA isolated from pasteurized camel milk found that a high proportion (10%) of MRSA were more heat resistant than a reference strain of S. aureus [60]. In contrast, other studies have found MRSA in heat-treated milk to be less heat tolerant to methicillin-susceptible S. aureus (MSSA) [53].…”
Section: Heat Resistance Of Amr Bacteriamentioning
confidence: 99%
“…However, it has been found that some of these tests can overestimate methicillin resistance (Olowe et al, 2013). Detection of the mecA gene using molecular methods seems to be the most reliable method of identifying MRSA and is considered as the ‘Gold Standard’ for methicillin resistance screening (Koupahi et al, 2016; Yehia et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Our results concerning the sensitivity of S. aureus to different antibiotics show multiple drug resistance, providing further evidence of a potential public and veterinary health hazard . Animals can also transmit resistant strains to humans [4,59,60].…”
Section: Resultsmentioning
confidence: 99%